Pemberian Pakan Alami Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Hulu’u (Giuris margaritaceus) - Julfikar Mile; Arafik Lamadi; Rully Tuiyo (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aimed to determine the growth and survival of Hulu’u fish using different natural feeds and identify the best natural feed for the growth and survival of Hulu’u fish. The study used a completely randomized design (CRD) consisting of four treatments and three replications, resulting in 12 experimental units. Each unit contained 15 Fish. Data collected included absolute weight growth, absolute length increase, and survival rate. The study was conducted for one month, with data collection performed four times during the study period. The average absolute weight was P2 (0,46 cm), P1 (0,38 cm), P3 (0,34 cm), and P4 (0,33 cm). The average absolute weight was P2 (0,42 grams), P1 (0, 34 grams), P3 (0,26 grams), and P4 (0, 25 grams). Survival Rates were P2 (60%), P1 (55,56%), P4 (51%), and P3 (46%). The ANOVA analysis showed that the F-value was greater than the F-table value of 5%, indicating that the treatments significantly affected the growth of Hulu’u fish. Different feeding for Hulu’u fish had an effect because the feeds provided were well consumed by the fish, resulting in good growth. Silkworm was the best feed, producing the highest absolute length increase of 0,46 cm and an absolute weight increase of 0,42 grams.